Sickle cell disease - Piel,FBJ; Steinberg,MH; Rees,DC (New England Journal of Medicine, 2017)
Sickle cell disease is an increasing global health problem. Estimates suggest that every year approximately 300,000 infants are born with sickle cell anemia, which is defined as homozygosity for the sickle hemoglobin (HbS) gene (i.e., for a missense mutation [Glu6Val, rs334] in the β-globin gene [HBB]) and that this number could rise to 400,000 by 2050.1 Although early diagnosis, penicillin prophylaxis, blood transfusion, transcranial Doppler imaging, hydroxyurea, and hematopoietic stem-cell transplantation can dramatically improve survival and quality of life for patients with sickle cell disease, our understanding of the role of genetic and nongenetic factors in explaining the remarkable phenotypic diversity of this mendelian disease is still limited. Better prediction of the severity of sickle cell disease could lead to more precise treatment and management. Beyond well-known modifiers of disease severity, such as fetal hemoglobin (HbF) levels and α-thalassemia, other genetic variants might affect specific subphenotypes. Similarly, although the influence of altitude and temperature has long been reflected in advice to patients with sickle cell disease, recent studies of nongenetic factors, including climate and air quality, suggest more complex associations between environmental factors and clinical complications.2 New treatments and management strategies accounting for these genetic and nongenetic factors could substantially and rapidly improve the quality of life and reduce health care costs for patients with sickle cell disease.